Halitosis as a symptom of gastroenterological diseases - Elżbieta Poniewierka; Maciej Pleskacz; Natalia Łuc-Pleskacz; Joanna Kłaniecka-Broniek (Gastroenterology Review)
Bad breath is a clinical symptom encountered by doctors of various specialties in their daily practice. The symptom causes lower self-esteem and a negative perception of the patient by society, and consequently personal and social isolation. Bad breath can be an early manifestation of many systemic diseases. Because its causes are numerous, it is important to properly diagnose the condition and apply the appropriate treatment. The aim of the study was to present the gastroenterological aspect of halitosis on the basis of available literature reports.